Information Asymmetry and Signalling in Emerging IPO Markets: The Case of Malaysia - Albada, Ali; Yong, Othman; Abdul-Rahim, Ruzita; Mat Hassan, Mohd. Ezani (Asian Journal of Business and Accounting, 2019)
Manuscript type: Research paper Research aims: This study examines the effect of information asymmetry on the relationship between the signalling variables and the initial returns of IPO. The signalling variables examined include lock-up period, underwriter reputation, auditor reputation, and board reputation. This study also examines the ability of signalling variables in reducing information asymmetry (the average first ten days of Bid/Ask spread is used as proxy for information asymmetry) around listing firm’s issues. Design/Methodology/Approach: This study employs cross-sectional regression model to examine the influencing effect of information asymmetry on the relationship between signalling variables and initial returns of IPOs, and to investigate which of the signals are able to reduce the level of information asymmetry surrounding the listing firm’s issues in the Malaysian IPO market. The study sample consists of 393 IPOs listed on Bursa Malaysia between January 2000 and December 2015. Research findings: The results show that the effect of signalling variables is more pronounced on the initial performance of IPOs when in an environment of high information asymmetry. Evidence also indicates that board reputation is able to reduce the under-pricing cost borne by listing firms by lowering the level of information asymmetry regarding the listing firm’s issues. Underwriter reputation is able to reduce the level of information asymmetry regarding listing firm’s issues, but unable to influence the initial returns of IPOs. Further, auditor reputation is able to reduce the under-pricing cost, but unable to reduce the level of information asymmetry regarding the listing firm’s issues. Finally, lock-up period is unable to reduce the level of information asymmetry as well as under-pricing with regards to the listing firm’s issues. Theoretical contribution/Originality: The effect of information asymmetry on the relationship between signalling variables and initial returns, and the effect of signalling variables on information asymmetry remains unexplored in the Malaysian IPO market. This gap is addressed by the current study. Practitioner/Policy implication: The findings imply that underwriter reputation, auditor reputation, and board member reputation are important for determining the initial returns of the IPOs. They are also important for reducing the level of information asymmetry surrounding the listing firm’s issues. Therefore, it is reasonable to suggest that information regarding these signals be disclosed completely to investors since current disclosure practices in Malaysia only embed fragmented information. Research limitation/Implications: In the present study, the Bid/ Ask spread is used as proxy for information asymmetry. Future studies should consider other indicators such as the heterogeneity of investors’ opinion on the true value of the listing firm’s issues. This is because the fixed price method provides no opportunity for prospective investors to reflect on their expectations and beliefs on the IPOs’ issue price. As such, the fixed-price offering will have higher divergence of opinions among investors when compared to other pricing mechanisms such as the book-building method. Keywords: Information Asymmetry, Initial Returns, Malaysia IPO Market, Signalling JEL Classification: D53, D82, G11, G02, G24, N25